PERILAKU KOMUNIKASI ETNIS TIONGHOA PERANAKAN DALAM BISNIS KELUARGA (Studi Fenomenologi mengenai Perilaku Komunikasi Etnis Tionghoa Peranakan dalam Bisnis Keluarga di Jakarta) - Firda Firdaus Abdi; Hanny Hafiar; Evi Novianti (Jurusan Ilmu Komunikasi UTM, 2015)
Peranakan Chinese is a result of marriage, assimilation, or acculturation between two major groups in Indonesia, the local and the Chinese. They are attached to various kinds of stereotypes that lead to difficulties in socializing, which ultimately affect their behaviors and on how they run the family business. The phenomenological approach research seeks to study the behavioral communications made by Peranakan Chinese who in running their family business. Five people who are Peranakan Chinese and have family business based in Jakarta are involved through some in-depth interviews and revealed that the meaning of peranakan itself are influenced by their experiences during socializing, which affects they way they acted up, including their behavioral communication in the family business to the obstacles encountered.Keywords: Crossbrreed Chinese, behavioral communications, family business